Ultrahigh-performance ice-based material and preparation method thereof
By using reinforced fibers, viscosity adjustment and gelling material design in ice-based materials, we jointly improve the strength of the matrix and additives, and solve the problems of low strength and high brittleness of existing ice-based materials, and achieve high strength, toughness and explosion-resistant ice-based composite materials.
Patent Information
- Application Number
- CN202510353517.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-25
AI Technical Summary
Existing ice-based materials have defects such as low strength and high brittleness in polar construction, which is difficult to meet the needs of large-scale construction.
Reinforced fibers, viscosity adjustment and gelling material design are adopted to improve the tensile strength and explosion resistance of ice-based composite materials by synergistically improving the strength of matrix and additive material strength, and the bonding between steel fibers and high-strength matrix is used to improve the tensile strength and explosion resistance of ice-based composite materials.
It significantly improves the strength, toughness and explosion resistance of ice-based materials, reduces material density, and enhances the uniformity and compressive strength of the materials.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ice-based materials, and in particular relates to an ultra-high performance ice-based material and a preparation method thereof. Background Art
[0002] Antarctica is rich in natural resources and has a special geographical location. Countries are planning to build infrastructure in Antarctica. The polar natural environment is extremely harsh, posing severe threats and challenges to equipment, facilities and personnel activities. Existing scientific research stations do not consider military weapons attacks, and are mostly built with prefabricated steel structures. However, the key to polar construction is to prevent attacks. The construction scale is large. For example, large-scale transportation of steel and cement construction materials from inland will have a very high cost, poor material durability, and easy exposure of strategic intentions in advance. It is extremely important to choose a construction material that is convenient for the local area. "Ice" is a natural and convenient material in Antarctica. Traditional ice has defects such as low strength and high brittleness, and is not suitable for large-scale construction. Studies have shown that adding a certain amount of wood pulp, sawdust, cotton and other materials to water can significantly improve the brittleness of ice and increase its strength. The present invention proposes an ice-based composite material with super mechanical properties, high toughness, ultra-high durability and excellent casting and molding properties and a preparation method thereof, which provide basic support for the construction of polar facilities. Summary of the invention
[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to propose an ultra-high performance ice-based material and a preparation method thereof, which are used to solve the problems of the prior art mentioned above. Reinforced fibers, viscosity adjustment and gelling material design are adopted to effectively reduce the material density and improve the uniformity of ice-based composite materials. By synergistically improving the strength of the matrix and the strength of the additives, the strength and toughness of the composite materials are effectively improved. Through the bonding effect between the steel fibers and the high-strength matrix, the tensile strength of the ice-based composite materials is effectively improved, the impact damage energy consumption is increased, and the explosion resistance is enhanced.
[0004] To achieve the above object, the present invention adopts the following technical scheme: an ultra-high performance ice-based material, comprising seawater, lightweight aggregate, a water-soluble thickener, a main material and an auxiliary material, the main material and the auxiliary material are stirred in a mixer, a thickening solution formed by seawater and the water-soluble thickener is added, and then the mixture is stirred again with the lightweight aggregate soaked in seawater to obtain a mixture, which is then molded and demolded after cooling to obtain an ultra-high performance ice-based material; The seawater is 80-90 parts by weight; The light aggregate is 3-5 parts by weight, and is a mixture of shale pottery sand and spherical high-strength light aggregate, wherein the shale pottery sand has a bulk density of ≤600kg / m³, a cylinder pressure strength of 5-7MPa, a particle size of 0.1-2mm, and continuous grading; the spherical high-strength light aggregate has a bulk density of ≤800kg / m³, a cylinder pressure strength of ≥25MPa, a particle size of 1-4.mm, and continuous grading; the weight of the spherical high-strength light aggregate is not less than 40% of the total weight of the light aggregate; The water-soluble thickener is 0.5 to 3 parts by weight, and the viscosity after thickening is ≥ 2000mpa; The main materials include silicon dioxide, fly ash microbeads and steel fibers; The auxiliary material is non-metallic fiber material.
[0005] The main materials are mixed in weight proportions as follows: 1-5 parts of silicon dioxide, 3-5 parts of fly ash microbeads, and 5-8 parts of steel fibers.
[0006] The steel fiber is a copper-plated steel fiber with a diameter of 0.18-0.22 mm, a length of 13-20 mm, and a tensile strength of ≥2500 MPa; the average particle size of the silicon dioxide is 10-50 nm, and the average particle size of the fly ash microbeads is 1-3 μm.
[0007] The non-metallic fiber comprises one or a combination of aramid fiber, sawdust fiber or cotton; the aramid fiber is 3-8 parts by weight, the sawdust fiber is 3-8 parts by weight, and the cotton is 0.95-1 part by weight.
[0008] A method for preparing an ultra-high performance ice-based material based on the above includes the following steps: Step 1: Weigh seawater, lightweight aggregate, water-soluble thickener, main ingredients and auxiliary materials according to the weight ratio, then pre-wet the lightweight aggregate, soak the lightweight aggregate in seawater for 12 hours, then fish it out and dry it until the saturated surface is dry to obtain pre-wet lightweight aggregate; calculate the water absorption of the pre-wet lightweight aggregate, and use the total water consumption to subtract the water absorption of the lightweight aggregate to obtain the net water consumption; Step 2: Add the main ingredients and auxiliary ingredients into a mixer and dry mix for 1 minute, then disperse the water-soluble thickener into the net water volume to form a thickening solution and add it into the mixer, and continue stirring for 2-3 minutes to make the slurry fully viscous and uniform to obtain a mixed material; wherein the mixer speed is greater than 100r / min; Step 3: Slowly add the pre-wetted lightweight aggregate in batches and stir for 5-15 minutes to evenly disperse the lightweight aggregate in the mixture to obtain a mixture; Step 4: Load the mixture into the test mold. Use a spatula to tamp along the inner wall of the test mold, and allow the mixture to slightly rise above the top of the test mold and rest for 5-10 minutes. Step 5: After molding, cover the surface of the test mold with a film to prevent water evaporation, and place it in an environment of -20℃ to -80℃ for 24 hours before demolding. The demolded specimen is placed in a cooling tank to obtain an ultra-high performance ice-based material.
[0009] The beneficial effects of the present invention are: 1. The synergy between the matrix strength and the aggregate strength is improved by using spherical high-strength lightweight aggregate, thereby effectively improving the strength of ice-based materials. The high-strength bonding force between steel fibers and the matrix is utilized to improve the tensile properties of ice-based materials, increase the energy consumption during the material destruction process, and thereby effectively reduce the degree of cracking and collapse damage on the back explosion surface of ice-based materials. In addition, the energy absorption effect of high-strength lightweight aggregate in ice-based materials also plays a positive role in improving the explosion resistance of the back explosion surface.
[0010] 2. The present invention uses silica, fly ash microbeads, aramid fiber, lightweight aggregate, wood fiber and cotton as toughening and reinforcing components of ice-based materials, which greatly reduces the apparent density of the system compared with traditional cement-based materials. On the other hand, by adding thickeners, the viscosity and fluidity of the slurry are improved, the floating of light fillers is effectively suppressed, and the uniformity of the materials after mixing is ensured. On the other hand, ice is selected as the matrix material, which has a wide range of sources and meets the demand for local materials. Ice-based materials do not require maintenance and can be used directly, which is conducive to ecological sustainable development. DETAILED DESCRIPTION
[0011] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.
[0012] The following embodiments are provided in conjunction with the present invention, but the present invention is not limited to the following embodiments: Embodiment 1:
[0013] An ultra-high performance ice-based material, the composition of the ice-based material by weight is as follows: 90 parts of seawater, 5 parts of lightweight aggregate, 3 parts of water-soluble thickener, the main material is 5 parts of silicon dioxide, 5 parts of fly ash microbeads, 8 parts of steel fiber, and the auxiliary material is 8 parts of sawdust fiber; The method for preparing the ultra-high performance ice-based material comprises the following steps: Step 1: Weigh seawater, lightweight aggregate, water-soluble thickener, main ingredients and auxiliary materials according to the weight ratio, then pre-wet the lightweight aggregate, soak the lightweight aggregate in seawater for 12 hours, then fish it out and dry it until the saturated surface is dry to obtain pre-wet lightweight aggregate; calculate the water absorption of the pre-wet lightweight aggregate, and use the total water consumption to subtract the water absorption of the lightweight aggregate to obtain the net water consumption; Step 2: Add the main ingredients and auxiliary ingredients into a mixer and dry mix for 1 minute, then disperse the water-soluble thickener into the net water volume to form a thickening solution and add it into the mixer, and continue stirring for 2-3 minutes to make the slurry fully viscous and uniform to obtain a mixed material; wherein the mixer speed is greater than 100r / min; Step 3: Slowly add the pre-wetted lightweight aggregate in batches and stir for 5-15 minutes to evenly disperse the lightweight aggregate in the mixture to obtain a mixture; Step 4: Load the mixture into the test mold. Use a spatula to tamp along the inner wall of the test mold, and allow the mixture to slightly rise above the top of the test mold and rest for 5-10 minutes. Step 5: After molding, cover the surface of the test mold with a film to prevent water evaporation, and place it in an environment of -20℃ to -80℃ for 24 hours before demolding. The demolded specimen is placed in a cooling tank to obtain an ultra-high performance ice-based material.
[0014] Embodiment 2: An ultra-high performance ice-based material, the composition of the ice-based material by weight is as follows: 80 parts of seawater, 3 parts of lightweight aggregate, 0.5 parts of water-soluble thickener, the main material is 3 parts of silicon dioxide, 3 parts of fly ash microbeads, 5 parts of steel fiber, and the auxiliary material is 3 parts of sawdust fiber; The method for preparing the ultra-high performance ice-based material comprises the following steps: Step 1: Weigh seawater, lightweight aggregate, water-soluble thickener, main ingredients and auxiliary materials according to the weight ratio, then pre-wet the lightweight aggregate, soak the lightweight aggregate in seawater for 12 hours, then fish it out and dry it until the saturated surface is dry to obtain pre-wet lightweight aggregate; calculate the water absorption of the pre-wet lightweight aggregate, and use the total water consumption to subtract the water absorption of the lightweight aggregate to obtain the net water consumption; Step 2: Add the main ingredients and auxiliary ingredients into a mixer and dry mix for 1 minute, then disperse the water-soluble thickener into the net water volume to form a thickening solution and add it into the mixer, and continue stirring for 2-3 minutes to make the slurry fully viscous and uniform to obtain a mixed material; wherein the mixer speed is greater than 100r / min; Step 3: Slowly add the pre-wetted lightweight aggregate in batches and stir for 5-15 minutes to evenly disperse the lightweight aggregate in the mixture to obtain a mixture; Step 4: Load the mixture into the test mold. Use a spatula to tamp along the inner wall of the test mold, and allow the mixture to slightly rise above the top of the test mold and rest for 5-10 minutes. Step 5: After molding, cover the surface of the test mold with a film to prevent water evaporation, and place it in an environment of -20℃ to -80℃ for 24 hours before demolding. The demolded specimen is placed in a cooling tank to obtain an ultra-high performance ice-based material.
[0015] Embodiment 3: An ultra-high performance ice-based material, the composition of the ice-based material by weight is as follows: 80 parts of seawater, 4 parts of lightweight aggregate, 1 part of water-soluble thickener, the main material is 5 parts of silicon dioxide, 3 parts of fly ash microbeads, 6 parts of steel fiber, and the auxiliary materials are 5 parts of sawdust fiber and 1 part of cotton; The method for preparing the ultra-high performance ice-based material comprises the following steps: Step 1: Weigh seawater, lightweight aggregate, water-soluble thickener, main ingredients and auxiliary materials according to the weight ratio, then pre-wet the lightweight aggregate, soak the lightweight aggregate in seawater for 12 hours, then fish it out and dry it until the saturated surface is dry to obtain pre-wet lightweight aggregate; calculate the water absorption of the pre-wet lightweight aggregate, and use the total water consumption to subtract the water absorption of the lightweight aggregate to obtain the net water consumption; Step 2: Add the main ingredients and auxiliary ingredients into a mixer and dry mix for 1 minute, then disperse the water-soluble thickener into the net water volume to form a thickening solution and add it into the mixer, and continue stirring for 2-3 minutes to make the slurry fully viscous and uniform to obtain a mixed material; wherein the mixer speed is greater than 100r / min; Step 3: Slowly add the pre-wetted lightweight aggregate in batches and stir for 5-15 minutes to evenly disperse the lightweight aggregate in the mixture to obtain a mixture; Step 4: Load the mixture into the test mold. Use a spatula to tamp along the inner wall of the test mold, and allow the mixture to slightly rise above the top of the test mold and rest for 5-10 minutes. Step 5: After molding, cover the surface of the test mold with a film to prevent water evaporation, and place it in an environment of -20℃ to -80℃ for 24 hours before demolding. The demolded specimen is placed in a cooling tank to obtain an ultra-high performance ice-based material.
[0016] Embodiment 4: An ultra-high performance ice-based material, the composition of the ice-based material by weight is as follows: 80 parts of seawater, 3 parts of lightweight aggregate, 1 part of water-soluble thickener, 5 parts of silicon dioxide as the main material, 3 parts of fly ash microbeads, 7 parts of steel fiber, and 8 parts of aramid fiber as the auxiliary material; The above-mentioned method for preparing ultra-high performance ice-based materials comprises the following steps: Step 1: Weigh seawater, lightweight aggregate, water-soluble thickener, main ingredients and auxiliary materials according to the weight ratio, then pre-wet the lightweight aggregate, soak the lightweight aggregate in seawater for 12 hours, then fish it out and dry it until the saturated surface is dry to obtain pre-wet lightweight aggregate; calculate the water absorption of the pre-wet lightweight aggregate, and use the total water consumption to subtract the water absorption of the lightweight aggregate to obtain the net water consumption; Step 2: Add the main ingredients and auxiliary ingredients into a mixer and dry mix for 1 minute, then disperse the water-soluble thickener into the net water volume to form a thickening solution and add it into the mixer, and continue stirring for 2-3 minutes to make the slurry fully viscous and uniform to obtain a mixed material; wherein the mixer speed is greater than 100r / min; Step 3: Slowly add the pre-wetted lightweight aggregate in batches and stir for 5-15 minutes to evenly disperse the lightweight aggregate in the mixture to obtain a mixture; Step 4: Load the mixture into the test mold. Use a spatula to tamp along the inner wall of the test mold, and allow the mixture to slightly rise above the top of the test mold and rest for 5-10 minutes. Step 5: After molding, cover the surface of the test mold with a film to prevent water evaporation, and place it in an environment of -20℃ to -80℃ for 24 hours before demolding. The demolded specimen is placed in a cooling tank to obtain an ultra-high performance ice-based material.
[0017] Embodiment 5: An ultra-high performance ice-based material, the composition of the ice-based material by weight is as follows: 85 parts of seawater, 3 parts of lightweight aggregate, 1 part of water-soluble thickener, the main material is 3 parts of silicon dioxide, 3 parts of fly ash microbeads, 5 parts of steel fiber, and the auxiliary material is 5 parts of aramid fiber; The preparation process of the above ultra-high performance ice-based material is as follows: Step 1: Weigh seawater, lightweight aggregate, water-soluble thickener, main ingredients and auxiliary materials according to the weight ratio, then pre-wet the lightweight aggregate, soak the lightweight aggregate in seawater for 12 hours, then fish it out and dry it until the saturated surface is dry to obtain pre-wet lightweight aggregate; calculate the water absorption of the pre-wet lightweight aggregate, and use the total water consumption to subtract the water absorption of the lightweight aggregate to obtain the net water consumption; Step 2: Add the main ingredients and auxiliary ingredients into a mixer and dry mix for 1 minute, then disperse the water-soluble thickener into the net water volume to form a thickening solution and add it into the mixer, and continue stirring for 2-3 minutes to make the slurry fully viscous and uniform to obtain a mixed material; wherein the mixer speed is greater than 100r / min; Step 3: Slowly add the pre-wetted lightweight aggregate in batches and stir for 5-15 minutes to evenly disperse the lightweight aggregate in the mixture to obtain a mixture; Step 4: Load the mixture into the test mold. Use a spatula to tamp along the inner wall of the test mold, and allow the mixture to slightly rise above the top of the test mold and rest for 5-10 minutes. Step 5: After molding, cover the surface of the test mold with a film to prevent water evaporation, and place it in an environment of -20℃ to -80℃ for 24 hours before demolding. The demolded specimen is placed in a cooling tank to obtain an ultra-high performance ice-based material.
[0018] The test was carried out in accordance with the relevant provisions of the "Technical Code for Engineering Sea Ice" (HY / T 047-2016), "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T50081-2019), "Reactive Powder Concrete" (GB / T31387-2015) and "Standard for Test Methods for Performance of Ordinary Concrete Mixtures" (GB / T 50080-2016), and the experimental temperature was -5°C.
[0019] Table 1 Basic performance test results of ice-based materials
[0020] It can be seen from the data in Table 1 that the compressive strength of the ultra-high performance ice-based material prepared by the present invention reaches more than 13.9 MPa, and the splitting tensile strength reaches more than 1.5 MPa. The effects of Examples 1-5 are significantly better than those of the comparative blank sample (pure ice). Although adding steel fiber to the material components will increase the material density, it can significantly improve the compressive strength and splitting tensile strength.
[0021] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
[0022] Parts of the present invention not described in detail are prior art.
Claims
1. An ultra-high performance ice-based material, characterized by: The method comprises seawater, lightweight aggregate, water-soluble thickener, main material and auxiliary material. The main material and auxiliary material are stirred in a mixer, a thickening solution formed by seawater and the water-soluble thickener is added, and then the mixture is stirred again with the lightweight aggregate soaked in seawater to obtain a mixture, and then molded and demolded after cooling to obtain an ultra-high performance ice-based material. The seawater is 80-90 parts by weight; The light aggregate is 3-5 parts by weight, and is a mixture of shale pottery sand and spherical high-strength light aggregate, wherein the shale pottery sand has a bulk density of ≤600kg / m³, a cylinder pressure strength of 5-7MPa, a particle size of 0.1-2mm, and continuous grading; the spherical high-strength light aggregate has a bulk density of ≤800kg / m³, a cylinder pressure strength of ≥25MPa, a particle size of 1-4.mm, and continuous grading; the weight of the spherical high-strength light aggregate is not less than 40% of the total weight of the light aggregate; The water-soluble thickener is 0.5 to 3 parts by weight, and the viscosity after thickening is ≥ 2000mpa; The main materials include silicon dioxide, fly ash microbeads and steel fibers; The auxiliary material is non-metallic fiber material.
2. The ultra-high performance ice-based material according to claim 1, characterized in that: The main materials are mixed in weight proportions as follows: 1-5 parts of silicon dioxide, 3-5 parts of fly ash microbeads, and 5-8 parts of steel fibers.
3. The ultra-high performance ice-based material according to claim 2, characterized in that: The steel fiber is a copper-plated steel fiber with a diameter of 0.18-0.22 mm, a length of 13-20 mm, and a tensile strength of ≥2500 MPa; the average particle size of the silicon dioxide is 10-50 nm, and the average particle size of the fly ash microbeads is 1-3 μm.
4. The ultra-high performance ice-based material according to claim 1, characterized in that: The non-metallic fiber comprises one or a combination of aramid fiber, sawdust fiber or cotton; the aramid fiber is 3-8 parts by weight, the sawdust fiber is 3-8 parts by weight, and the cotton is 0.95-1 part by weight.
5. The ultra-high performance ice-based material according to claim 1, characterized in that: An ultra-high performance ice-based material includes: 90 parts of seawater, 5 parts of lightweight aggregate, 3 parts of water-soluble thickener, 5 parts of silicon dioxide as the main material, 5 parts of fly ash microbeads, 8 parts of steel fiber, and 8 parts of sawdust fiber as the auxiliary material.
6. The ultra-high performance ice-based material according to claim 1, characterized in that: An ultra-high performance ice-based material includes: 80 parts of seawater, 3 parts of lightweight aggregate, 0.5 parts of water-soluble thickener, 3 parts of silicon dioxide as the main material, 3 parts of fly ash microbeads, 5 parts of steel fiber, and 3 parts of sawdust fiber as the auxiliary material.
7. The ultra-high performance ice-based material according to claim 1, characterized in that: An ultra-high performance ice-based material includes: 80 parts of seawater, 4 parts of lightweight aggregate, 1 part of water-soluble thickener, 5 parts of silica as the main material, 3 parts of fly ash microbeads, 6 parts of steel fiber, and 5 parts of sawdust fiber and 1 part of cotton as the auxiliary materials.
8. The ultra-high performance ice-based material according to claim 1, characterized in that: An ultra-high performance ice-based material includes: 80 parts of seawater, 3 parts of lightweight aggregate, 1 part of water-soluble thickener, 5 parts of silicon dioxide as the main material, 3 parts of fly ash microbeads, 7 parts of steel fiber, and 8 parts of aramid fiber as the auxiliary material.
9. The ultra-high performance ice-based material according to claim 1, characterized in that: An ultra-high performance ice-based material includes: 85 parts of seawater, 3 parts of lightweight aggregate, 1 part of water-soluble thickener, 3 parts of silica as the main material, 3 parts of fly ash microbeads, 5 parts of steel fiber, and 5 parts of aramid fiber as the auxiliary material.
10. A method for preparing an ultra-high performance ice-based material according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1: Weigh seawater, lightweight aggregate, water-soluble thickener, main ingredients and auxiliary materials according to the weight ratio, then pre-wet the lightweight aggregate, soak the lightweight aggregate in seawater for 12 hours, then fish it out and dry it until the saturated surface is dry to obtain pre-wet lightweight aggregate; calculate the water absorption of the pre-wet lightweight aggregate, and use the total water consumption to subtract the water absorption of the lightweight aggregate to obtain the net water consumption; Step 2: Add the main ingredients and auxiliary ingredients into a mixer and dry mix for 1 minute, then disperse the water-soluble thickener into the net water volume to form a thickening solution and add it into the mixer, and continue stirring for 2-3 minutes to make the slurry fully viscous and uniform to obtain a mixed material; wherein the mixer speed is greater than 100r / min; Step 3: Slowly add the pre-wetted lightweight aggregate in batches and stir for 5-15 minutes to evenly disperse the lightweight aggregate in the mixture to obtain a mixture; Step 4: Load the mixture into the test mold. Use a spatula to tamp along the inner wall of the test mold, and allow the mixture to slightly rise above the top of the test mold and rest for 5-10 minutes. Step 5: After molding, cover the surface of the test mold with a film to prevent water evaporation, and place it in an environment of -20℃ to -80℃ for 24 hours before demolding. The demolded specimen is placed in a cooling tank to obtain an ultra-high performance ice-based material.
Citation Information
Patent Citations
High-performance bamboo fiber composite ice material and preparation method thereof
CN107990612A
Explosion-resistant lightweight high-performance concrete and preparation method thereof
CN114933453A
Organic fiber reinforced composite ice material as well as preparation method and application thereof
CN117450704A
Abrasion-resistant strengthening method for compacted snow runway pavement of polar region airport
CN118407313A
Dumbbell-shaped coarse aggregate, preparation method thereof and ice-based composite material
CN118495843A